"Vivere omnes beate volunt..." Seneca és a Tabula Cebetis párhuzamai = "To live happily is the desire of all men..." : Parallels between Seneca and the Tablet of Cebes - Janzsó Miklós (2019)
In this paper I tried to demonstrate parallels between the works of Seneca the Younger, and the socalled Tabula Cebetis. This short dialogue from the first century AD contains moral teachings about reaching true happiness. Contemporary authors like Lucian, Dio Chrysostom and Plutarch are the closest parallels in using allegories and phrases, but the ethical teaching of Seneca is the most comparable with the whole teaching of the Tabula Cebetis. I tried to highlight some phrases which can prove the similarity of the thoughts of both authors. The works of Seneca may also provide a clue to reveal the author of this anonymous work.